The Effect of Spaced Repetition Learning Through Anki on Medical Board Exam Performance - Spencer Cooper; Nicole Twardowski; Michael Vogel; Daniel Perling; Rebecca Ryznar (University Library System, University of Pittsburgh, 2023)
Background: Spaced repetition learning is a method of learning that relies on a fixed formula for spacing out flashcards to ensure long term retention of a topic. Anki is one such application available online that utilizes spaced repetition learning. This retrospective cohort study analyzed incorporating Anki with medical school curriculum and its effect on board examination scores. The hypothesis is that students who engaged in spaced repetition learning through Anki scored higher on licensing board exams and achieved higher GPAs than students who did not engage with this method. Methods: The hypothesis was tested through comparison of USMLE Step 1 scores, COMLEX Level 1 scores, and GPA. The samples were selected from the Rocky Vista University Class of 2023 and split between 35 students in the Anki Cohort and 268 students in the non-Anki cohort. Results: 1 (2.8%) student failed USMLE Step 1 in the Anki cohort compared to 28 (10.94%) students who failed Step 1 in the non-Anki cohort (p > 0.05) The Anki cohort achieved a higher mean USMLE Step 1 (223.71 versus 222.58) and COMLEX Level 1 (569.51 versus 559.99). The non-Anki cohort had a higher GPA (85.60) than the Anki cohort (83.82) (p < 0.01). Conclusion: This is the first study to evaluate for a correlation between COMLEX level 1 scores with use of spaced repetition learning. Although this study was unable to find any significant correlation between Anki use and licensing exam scores, further investigations with better control and sample size are needed.